Biodiversity And Arthropod Abundance In Organic Semi Rice In Swamp Lowland in Palangka Raya City - Manaf, Melhanah; Mulyani, Rahmawati Budi; Satrio, Mario (Akta Agrosia, 2021)
Palangka Raya has the potential for swamp lowland to be used for rice farming. For this purpose, knowledge of arthropod biodiversity is required. The study aims to determine the biodiversity and abundance of arthropods and arthropods dominant in semi-organic rice plantations in swamp lowlands. The study was conducted from September to November 2019 in Palangka Raya City. The study was carried out on 1.148m2 farmer's paddy fields. The land is divided into three trial plots, each measuring 28x13 m2. Observations were made at the age of 8-15 WAP. Samples were taken using a net trap (Sweep net). Arthropod biodiversity was analyzed using the Shannon-Weaver diversity index (H'). The results showed that in the semi-organic rice ecosystem were obtained 10 orders, 58 families with a total of 8973 individuals, consisting of pests 92.61%, predators 6.59%, parasitoids 0.28%, pollinators 0.06%, Detrivore 0.35%, and 0.07% neutral insects. Diversity index (H') is low to moderate (0.10-2.19), dominance index (C) is in the low to high (0.18-0.97); Evenness index shows that the community is depressed until unstable (0.04-0.67); and The abundance index on the criteria of less to very much (8.96-25.03). The dominant arthropods are dominated by the Rice bug (Leptocorisa acuta).